PENINGKATAN KETERAMPILAN MENARI DENGAN PENGGUNAAN METODE DRILL BAGI SISWA KELAS III SEKOLAH DASAR - Nofrita, Rosa (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study was to describe the planning, execution and assessment of improved dancing skills use drill method for third grade students. Type of this research was Classroom Action Research. The results of assessment dancing skills have the average value were 65.9 in the first cycle and the second cycle increase to 77.8. Thus, it can be concluded that using drill method in teaching dancing to third grade students can improve their skills. Kata Kunci : keterampilan; menari; dan metode drill.